2016
DOI: 10.7322/jhgd.119293
|View full text |Cite
|
Sign up to set email alerts
|

Fruit intake and obesity Fruit and vegetables consumption and obesity in Brazil

Abstract: Introduction: Obesity affects more than half of the adult population and correlates with the development of chronic and psychosocial diseases. The consumption of fruits and vegetables (FV) is a protective factor for obesity, but their consumption is often below the recommendations. Objective:To identify the level of fruit consumption in human development cycles, as well as the data on the association of fruit consumption with excess weight in Brazil. Methods:A non-systematic literature review on the Virtual He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
3
5
0
5
Order By: Relevance
“…The same survey indicates that the prevalence of overweight in adult women in Rio Branco is 55.8% (95% CI: 52.2-59.5%) and that of obese adult women is 22.8% (95% CI: 19.7-25.9%), classifying this city as the most obese capital in the country and suggesting an inverse association between obesity and regular consumption of fruits, vegetables and vegetables [34]. This association is consistent with the results of a review of 23 Brazilian studies on the association between fruit and vegetable intake and overweight in children, adolescents, and adults [35].…”
Section: Discussionsupporting
confidence: 83%
“…The same survey indicates that the prevalence of overweight in adult women in Rio Branco is 55.8% (95% CI: 52.2-59.5%) and that of obese adult women is 22.8% (95% CI: 19.7-25.9%), classifying this city as the most obese capital in the country and suggesting an inverse association between obesity and regular consumption of fruits, vegetables and vegetables [34]. This association is consistent with the results of a review of 23 Brazilian studies on the association between fruit and vegetable intake and overweight in children, adolescents, and adults [35].…”
Section: Discussionsupporting
confidence: 83%
“…The same survey indicates that the prevalence of overweight in adult women in Rio Branco is of 55.8% (95% CI: 52.2% -59.5%) and obese adult women is of 22.8% (95% CI: 19, 7% -25.9%), classifying this city as the most obese capital in the country and suggesting an inverse association between obesity and regular consumption of fruits, vegetables and vegetables (33). This association is consistent with the results of a review of 23 Brazilian studies on the association between fruit and vegetable intake and overweight in children, adolescents and adults (34).…”
Section: Discussionsupporting
confidence: 91%
“…At least 50% of the population consumes half or more of the recommended level of vegetables (200g/day). In Brazil, the prevalence of adequate consumption of fruits and vegetables is low in all regions and among all age groups; the highest prevalence is found among women and increases with age, higher education level and higher socioeconomic status 47 . Similar to the findings of this study, gender differences in fruits and vegetables consumption have been shown in several studies, with women at an advantage 20,46,48 .…”
Section: Discussionmentioning
confidence: 99%